Anti-cancer effect of lactic acid bacteria expressing antioxidant enzymes or IL-10 in a colorectal cancer mouse model - del Carmen, Silvina Andrea (2017)
The association between inflammatory bowel diseases and colorectal cancer is well documented. The genetic modification of lactic acid bacteria as a tool to increase the anti-inflammatory potential of these microorganisms has also been demonstrated. Thus the aim of the present work was to evaluate the anti-cancer potential of different genetically modified lactic acid bacteria (GM-LAB) producing antioxidant enzymes (catalase or superoxide dismutase) or the anti-inflammatory cytokine IL-10 (protein or DNA delivery) using a chemical induced colon cancer murine model. Dimethilhydrazine was used to induce colorectal cancer in mice. The animals received GM-LAB producing anti-oxidant enzymes, IL-10 or a mixture of different GM-LAB. Intestinal damage, enzyme activities and cytokines were evaluated and compared to the results obtained from mice that received the wild type strains from which derived the GM-LAB. All the GM-LAB assayed showed beneficial effects against colon cancer even though they exerted different mechanisms of action. The importance to select LAB with innate beneficial properties as the progenitor strain was demonstrated with the GM-LAB producing anti-oxidant enzymes. In addition, the best effects for the mixtures GM-LAB that combine different anti-inflammatory mechanism. Results indicate that mixtures of selected LAB and GM-LAB could be used as an adjunct treatment to decrease the inflammatory harmful environment associated to colorectal cancer, especially for patients with chronic intestinal inflammation who have an increased risk to develop colorectal cancer.